Interactive Multimedia as a Modern Instructional Solution in the Digital Era: Arabic Language Edition - Azkari, Al Wasikotul Baroroh (An Nazhair: Journal of Arabic Education, 2025)
The digital era demands educational innovation, with interactive multimedia emerging as a modern instructional solution. Interactive multimedia integrates text, audio, video, animations, and interactive elements to create dynamic, engaging, and effective learning experiences. This article examines the role of interactive multimedia in addressing the limitations of conventional teaching materials, such as low student engagement, difficulties in understanding abstract concepts, and limited access to learning resources. Through a literature review approach, this study explores the benefits of interactive multimedia, including enhanced learning motivation, deeper conceptual understanding, and flexibility for self-paced learning. It also discusses implementation challenges, such as infrastructure gaps, teacher competency, and the need for high-quality content development. The analysis demonstrates that interactive multimedia not only improves learning outcomes but also prepares students for 21st-century digital literacy demands. The article concludes that adopting interactive multimedia as modern instructional materials is a strategic step toward creating inclusive, adaptive, and student-centered learning in the digital age. Recommendations include teacher training, multi-stakeholder collaboration, and curriculum-aligned content development.